CREATION AND TRANSFORMATION OF BARONGAN LEMPUNG IN BLORA - Muksin Muksin; Dharsono Dharsono; Sri Hastanto; Nuning Y. Damayanti (Institut Seni Indonesia Surakarta, 2020)
Barongan is a ritual medium in the rituals of the sacred traditional ceremonies. Its shape and character emit a scary and frightening aura. Children Blora make artificial barongan become barongan lempung as toys. This study focuses on the issue of transformation in the barongan lempung Blora. This study uses a qualitative approach with direct observation methods, interviews, artifact data and literature studies. Data analysis uses an interactive analysis approach. The results of the study showed that: (1) The existence of the mask barongan is in the heart’s of Blora people, has the form of a sacred, fierce and frightening, but its presence is always eagerly awaited by adults to children as entertainment; (2) the mask barongan gives a distinct impression in the hearts of children, so that barongan sacred inspires the emergence of barongan lempung (clay mask) as their toys; (3) The shape of the barongan lempung is created by imitating it directly from the original barongan.